Optical interferometric technique for induced strain ferroelectric loop study at low frequency - Siripong Somwan (2018)
Michelson interferometric technique was modified in the setup and used to measure very small changes in optical path length for electric field induced-strain phenomena. Induced-strain is established in the sample when the beam of light propagating through the sample surface undergoes a shift in phase, which in turn leads to a change in the intensity of the interference pattern formed where the reference and probing beams recombine. In this work the electric field induced-strain was measured as a function of electric field (s-E loop) and polarization (s-P loop) of PbMg 1/3 Nb 2/3 O 3 (PMN) and 0.7PbMg 1/3 Nb 2/3 O 3 -0.3PbZr 0.52 Ti 0.48 O 3 (0.7PMN-0.3PZT) ceramics, which showed electrostrictive (quadratic shape curve) and piezoelectric (butterfly shape curve) behavior at various frequency (0.01-1Hz). © (2014) Trans Tech Publications, Switzerland.